The mastery lifestyle intervention to reduce biopsychosocial risks for pregnant Latinas and African Americans and their infants: protocol for a randomized controlled trial - R. Jeanne Ruiz; Kristyn Grimes; Elizabeth Spurlock; Angela Stotts; Thomas F. Northrup; Yolanda Villarreal; Robert Suchting; Melissa Cernuch; Liza Rivera; Raymond P. Stowe; Rita H. Pickler (BMC, 2022)
Abstract Background Pregnant Mexican Americans (hereafter called Latinas) and Black/African American women are at increased risk for psychological distress, contributing to preterm birth and low birthweight; acculturative stress combined with perceived stress elevates depressive symptoms in Latinas. Based on our prior research using a psychoneuroimmunology framework, we identified psychological and neuroendocrine risk factors as predictors of preterm birth in Latina women that are also identified as risk factors for Black/African American women. Methods/design In this prospective, randomized controlled trial with parallel group design we will explore psychosocial, neuroendocrine, and birth outcome effects of the Mastery Lifestyle Intervention (MLI). The MLI is a culturally relevant, manualized, psychosocial, group intervention integrating two cognitive behavioral therapies for both pregnant Latinas and Black/African American women (total n = 221). Study inclusion criteria are: women with current pregnancy at 14-20 weeks gestation, ability to read and speak English or Spanish, self-identify as Latina of Mexican heritage or Black/African American, 18-45 years old, born in the US or Mexico, and currently living in the US. Participants must receive Medicaid or other government-supported insurance, and meet screening criteria for anxiety, depressive symptoms, or stress. Participants are randomly assigned to either the intervention (MLI) or usual care group (UCG) in groups of 6-8 participants that occur over 6 consecutive weeks. Data are collected at 3 time points: enrollment (14-20 weeks gestation), following treatment (20-26 weeks), and 6 weeks after treatment (32-36 weeks gestation). Additional outcome, mediating, and moderating data are collected from the electronic health record during pregnancy and at birth. Analyses will primarily use generalized linear mixed modeling (GLMM) to evaluate the relationships between predictors and outcomes. Discussion This RCT will test the efficacy of two combined third generation cognitive behavioral therapies (the MLI), given in a group format over 6 sessions, as compared to a usual prenatal care group, for both Latina and African American pregnant women. If efficacious, it may be provided as an adjunct to routine prenatal care and improve mental health, as well as babies being born too small and too soon. Trial registration The trial was retrospectively registered at ClinicalTrials.gov . Bethesda (MD): National Library of Medicine. Identifier NCT05012072 , Reducing Pregnancy Risks: The Mastery Lifestyle Intervention (MLI); August 19, 2021. The trial is currently recruiting participants.